Correction: Gvozdenović et al. Impact of Vitamin D Status and Nutrition on the Occurrence of Long Bone Fractures Due to Falls in Elderly Subjects in the Vojvodina Region of Serbia. Nutrients 2024, 16 , 2702. - Gvozdenović, Nemanja; Šarac, Ivana; Ćorić, Andrijana; Karan, Saša; Nikolić, Stanislava; Ždrale, Isidora; Milešević, Jelena (Nutrients, 2026)
This article focuses on correcting previously published data regarding vitamin D and calcium intake and serum vitamin D levels in elderly subjects with and without fractures in the Vojvodina region, Serbia. The corrected results show that serum vitamin D levels were significantly lower in the fracture group (median 23.0 nmol/L) compared to controls (median 76.0 nmol/L), and that a high percentage of subjects in both groups did not meet the recommended dietary intakes for vitamin D and calcium according to the European Food Safety Authority (EFSA) and the Institute of Medicine (IOM). Specifically, 90.5% of the fracture group had vitamin D intake below 5 µg/day, and 94.3% did not meet the IOM calcium intake recommendation of 1200 mg/day. The corrections clarify numerical errors but do not affect the study’s scientific conclusions.